Answer:
b) p=26
Step-by-step explanation:
3p + 3 · 8 = 2 ·2p - 2
3p + 24 = 4p - 2
p = 26
Answer:
1 solution.
General Formulas and Concepts:
<u>Pre-Algebra</u>
Step-by-step explanation:
<u>Step 1: Define equation</u>
9(z + 8) = -9z - 72
<u>Step 2: Solve for </u><em><u>x</u></em>
- Distribute 9: 9x + 72 = -9z - 72
- Add 9z to both sides: 18z + 72 = -72
- Subtract 72 on both sides: 18z = -144
- Divide 18 on both sides: z = -8
Here we see that we will get only 1 solution for <em>z</em>.
Answer:
The answer is don't ask me to explain cuz i can't O.O
but there yea go :3
Step-by-step explanation:
It is the third one because it equals the same as 8 times 54 . I hope this helped